2005
DOI: 10.1111/j.1471-0528.2005.00579.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of matrix metalloproteinases in preterm labour

Abstract: Extracellular matrix homeostasis is a key process in the maintenance of the tensile strength of the amniochorion. This tensile strength guarantees the role of the membranes as a physical and functional boundary for the fetus during human pregnancy. Pathological rupture of these structures before 37 completed weeks of gestation is known as preterm prelabour rupture of the membranes (PPROM) and it is a major cause of spontaneous preterm labour and preterm birth. A mechanism involving the activation of matrix met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(121 citation statements)
references
References 11 publications
3
115
0
3
Order By: Relevance
“…PGs contribute to the physiological inflammatory reaction seen in labour; for example PGE 2 enhances migration of leukocytes towards the cervix, which in turn leads to an increased production of IL-8 (Hertelendy & Zakár 2004). PGF 2α indirectly can activate IL-1β in the decidua and consequently increase production of MMP-9 (Christiaens et al 2008), which is known to participate in breakdown of the extracellular matrix leading to ruptured foetal membranes (Vadillo-Ortega & Estrada-Gutiérrez 2005). Additionally, PGE 2 interacts with LPS to induce IL-6, COX-2 and IL-1β via EP 4 on macrophages (Aoki & Narumiya 2012) indicating PGs' role in infection associated PTL.…”
Section: Pg/pg Receptors and Cytokinesmentioning
confidence: 99%
“…PGs contribute to the physiological inflammatory reaction seen in labour; for example PGE 2 enhances migration of leukocytes towards the cervix, which in turn leads to an increased production of IL-8 (Hertelendy & Zakár 2004). PGF 2α indirectly can activate IL-1β in the decidua and consequently increase production of MMP-9 (Christiaens et al 2008), which is known to participate in breakdown of the extracellular matrix leading to ruptured foetal membranes (Vadillo-Ortega & Estrada-Gutiérrez 2005). Additionally, PGE 2 interacts with LPS to induce IL-6, COX-2 and IL-1β via EP 4 on macrophages (Aoki & Narumiya 2012) indicating PGs' role in infection associated PTL.…”
Section: Pg/pg Receptors and Cytokinesmentioning
confidence: 99%
“…As gestation progresses, programmed collagenolysis takes place, which is mediated by matrix metalloproteinase (MMP) enzymes. A decrease in the collagen content of the membranes and activation of MMPs occurs during labour (Hampson et al 1997, Goldman et al 2003, and inappropriate or premature MMP expression and activity is proposed to contribute to the pathological preterm premature rupture of membranes (PPROM) (Vadillo-Ortega & Estrada-Gutierrez 2005). ECM collagen degradation during cervical ripening occurs in order to allow the cervix to become soft and distensible, thereby accommodating the passage of the fetus during labour.…”
Section: Nf-kb Regulates Matrix Metalloproteinase Expressionmentioning
confidence: 99%
“…The onset of labour is associated with an influx of inflammatory cells into the membranes, decidua and cervix (Osman et al 2003), and MMPs found within the uterus may derive from these infiltrating leukocytes (Vadillo-Ortega & Estrada-Gutierrez 2005). The chemokine IL-8 is largely responsible for the influx of leukocytes into uterine tissues, where it induces their degranulation and release of MMPs (Osmers et al 1995).…”
Section: Nf-kb Regulates Matrix Metalloproteinase Expressionmentioning
confidence: 99%
“…Fetal membranes that rupture prematurely have reduced collagen content, which could be the result of diminished synthesis or increased catabolism (Skinner et al, 1981;Hampson et al, 1997;Vadillo-Ortega et al, 1990;Wang et al, 2004;Fujimoto et al, 2002;Ferrand et al, 2002;Vadillo-Ortega & Estrada-Guiterrez, 2005;Moore et al, 2006). The SERPINH1 gene (*600943, collagen-binding protein 2 (CBP2)), which encodes heat-shock protein 47 (Hsp47), an intracellular chaperone for collagen proteins, plays a key role in governing collagen production in that levels of Hsp47 are directly correlated with collagen synthesis.…”
Section: Introductionmentioning
confidence: 99%